Study on Precast Coconut Shell Concrete Beam-Column Junction Using M-Sand under Static Load - Ramasubramani, R.; Gunasekaran, K. Gunasekaran (International Journal of Integrated Engineering, 2020)
Coconut shell (CS) is one of the sustainable alternative aggregates and coconut shell concrete (CSC) was developed a decade earlier. Prefabricated conventional concrete (CC) and CSC using M-sand, and their research are very limited. Capacity and behavior of the joints are important in precast. Hence in this study, precast column-beam behavior of CSC elements was studied. Two different sizes 12 and 16 mm bolts and nuts connection were chosen and used to connect the precast elements. Also the same sectional details were used and specimens produced for combination with CC using M-sand (CCM). Specimen failure of both monolithic and prefabricated CSC using M-sand (CSCM) elements was typical structural failure and is comparable to that of CCM. Compared to CCM, high deflection was observed on CSCM element. No crack was developed on both CCM and CSCM prefabricated specimen. All elements were able to sustain their maximum potential for strain. Column-beam joint behavior of CSCM monolithic and prefabricated specimen behavior are comparable to that of CCM.